2015
DOI: 10.1002/jsfa.7080
|View full text |Cite
|
Sign up to set email alerts
|

Thyme and basil essential oils included in edible coatings as a natural preserving method of oilseed kernels

Abstract: Thyme and basil essential oils added to the CMC coating improved the sensory stability of this product during storage, but only thyme essential oil increased their chemical stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 32 publications
(63 reference statements)
2
21
0
Order By: Relevance
“…Previous studies on edible films enriched with antioxidant compounds reported protective effects on the food product studied (Eça and others ; Riveros and others ). Ponce and others studied different edible films (chitosan, CMC, among others) enriched with oleoresins.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Previous studies on edible films enriched with antioxidant compounds reported protective effects on the food product studied (Eça and others ; Riveros and others ). Ponce and others studied different edible films (chitosan, CMC, among others) enriched with oleoresins.…”
Section: Resultsmentioning
confidence: 82%
“…It is an important industrial polymer with a wide range of applications in flocculation, detergents, textiles, papers, foods, and drugs. Recently, it has been used in edible films on different foods, improving their shelf life (Baldwin and others ; Tongdeesoontorn and others ; Riveros and others ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the recent years, much of the interest has developed in naturally occurring antioxidants, because of the adverse attention received by the synthetic antioxidants, and because of the worldwide trend to avoid or minimize the use of artificial food additives (Filiz and Seydim, 2014;Gad and Sayd, 2015;Saral et al, 2014). Also the use of natural antioxidants for frying purposes has increased during the last few years (Bera et al, 2006;Budak et al, 2015;Riveros et al, 2015;Urbancic et al, 2014). Plant extracts, especially antioxidants obtained from herbs and spices, have been proposed for stabilizing frying oils.…”
Section: Introductionmentioning
confidence: 99%
“…These results provide evidence that there is a protective effect against sensory product deterioration, as both these sensory attributes are related to lipid oxidation (Nepote and others ; Quiroga and others ). An increase in the intensity ratings of oxidized and cardboard flavors have been observed in other products coated with edible films, including roasted peanuts (Riveros and others , ) and roasted almonds (Larrauri and others ). These studies also reported a protective effect of the coating against product deterioration.…”
Section: Resultsmentioning
confidence: 73%
“…It is evident that the addition of the MC coating helped to preserve this sensory attribute in walnuts. Riveros and others (, ) reported that edible films helped to preserve the peanut flavor in roasted peanuts, and the sunflower flavor in roasted sunflower kernels. Larrauri and others () also reported that edible films helped to preserve the almond flavor in roasted almonds.…”
Section: Resultsmentioning
confidence: 99%